The good, the bad and the very slimy - Stine, R. L; Park, Trip (New York HarperCollins, 2005)
Rotten School's bad boy, Bernie B., is trying to turn over a new leaf in order to date the prettiest girl in school, but he may trip over his own slime trail
"A Parachute Press book."
Includes 4 really rotten stickers
Ages 8-12
2
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Slugs (Mollusks) -- Fiction